(untitled) (Scientific journal of the Fergana State University, 2026)
In this work, the influence of deep impurity levels on the photosensitivity of CdTe-SiO₂-Si heterostructures synthesized by thermal evaporation and subsequent annealing is considered. The presence and energy position of deep level defects in the CdTe layer were determined by temperature-dependent photoresponse and deep level transient spectroscopy. Our results show that the inclusion of deep impurity levels significantly changes the dynamics of photocarrier generation and recombination, leading to an increase in photosensitivity under sub-band illumination. In addition, a correlation between the type and concentration of deep level states and the spectral dependence of the photoresponse is shown. The results obtained are of great importance for the optimization of CdTe-based heterostructures in optoelectronic applications, including infrared photodetectors and solar cells.